Factors Influencing Nurse Retention in Conflict Zones: A Systematic Review - Clara Cassandra Resubun; Ferry Efendi; Sylvia Dwi Wahyuni (Indonesian Journal of Global Health Research, 2025)
Nurse retention in conflict zones remains a critical global issue, significantly influencing the sustainability of healthcare services. Nurses in these areas face numerous challenges, including safety risks, emotional stress, and inadequate compensation, which impact their decision to continue working in such environments. This systematic review aims to identify and analyze factors influencing nurse retention in conflict zones and propose intervention strategies to address these challenges. A systematic review was conducted following PRISMA guidelines. Data were extracted from Scopus, PubMed, Web of Science, and CINAHL databases. Studies focusing on nurse retention in conflict zones were included, with data extraction guided by the PICOS framework. The quality of the included studies was assessed using Joanna Briggs Institute tools. A total of fifteen studies were reviewed, identifying key factors for nurse retention. These include improved working conditions, adequate safety measures, financial incentives (e.g., risk allowances), and emotional support systems. Job satisfaction, influenced by job security and a supportive work environment, was also a significant determinant of retention. Emotional and psychological support systems were found to reduce burnout, thereby fostering nurse retention. A multifaceted approach, incorporating improved working conditions, enhanced financial incentives, and robust emotional support, is essential for retaining nurses in conflict zones. Future research should focus on the long-term impact of these strategies and their adaptation to region-specific needs.